2018
DOI: 10.1038/s41467-018-03570-9
|View full text |Cite
|
Sign up to set email alerts
|

A lever-like transduction pathway for long-distance chemical- and mechano-gating of the mechanosensitive Piezo1 channel

Abstract: Piezo1 represents a prototype of eukaryotic mechanotransduction channels. The full-length 2547-residue mouse Piezo1 possesses a unique 38-transmembrane-helix (TM) topology and is organized into a three-bladed, propeller-shaped architecture, comprising a central ion-conducting pore, three peripheral blade-like structures, and three 90-Å-long intracellular beam-resembling structures that bridge the blades to the pore. However, how mechanical force and chemicals activate the gigantic Piezo1 machinery remains elus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
223
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(226 citation statements)
references
References 47 publications
3
223
0
Order By: Relevance
“…On the basis of the identification of the transmembrane gate located in the inner helix (IH) and the cytosolic lateral plug gates that physically block the three lateral ion-conducting portals (Geng et al, 2020), we have proposed that Piezo channels might utilize a dual-gating mechanism, in which the transmembrane gate is dominantly controlled by the top extracellular cap , while the lateral plug gates are controlled by the peripheral blade-beam apparatus via a plug-and-latch mechanism (Geng et al, 2020;Wang et al, 2019;Wang et al, 2018;Zhao et al, 2018a;Zhao et al, 2018b) (Figure 7A, B). The cap domain is embedded in the center of the nano-bowl shaped by the curved Piezo1-membrane system and sits right on the top of the transmembrane pore of Piezo1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of the identification of the transmembrane gate located in the inner helix (IH) and the cytosolic lateral plug gates that physically block the three lateral ion-conducting portals (Geng et al, 2020), we have proposed that Piezo channels might utilize a dual-gating mechanism, in which the transmembrane gate is dominantly controlled by the top extracellular cap , while the lateral plug gates are controlled by the peripheral blade-beam apparatus via a plug-and-latch mechanism (Geng et al, 2020;Wang et al, 2019;Wang et al, 2018;Zhao et al, 2018a;Zhao et al, 2018b) (Figure 7A, B). The cap domain is embedded in the center of the nano-bowl shaped by the curved Piezo1-membrane system and sits right on the top of the transmembrane pore of Piezo1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis reveals large conformational changes of the highly curved blades, which might be converted to the cytosolic lateral plug gates via a lever-like motion of the featured beam structure (Fig. 7A, B) (Geng et al, 2020;Wang et al, 2019;Wang et al, 2018;Zhao et al, 2018a). Using the probe of an atomic force microscope to apply force to the Piezo1 channel reconstituted in lipid bilayers, Lin et al have elegantly demonstrated that the highly curved blade can undergo reversible flattening at biologically relevant pressures (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculated about a potential relationship between Piezo1 and Notch1, using endothelial cells to investigate this idea because both proteins are prominent in these cells and have established functional significance in them 1,[8][9][10]12,19 . Because mechanical force can affect numerous mechanisms, we explored the relationship by specifically activating Piezo1 channels with a synthetic small-molecule agonist (Yoda1) that acts directly to enhance force sensitivity [21][22][23][24] . Because there is inherent force in cell membranes and force arises through cell-cell and cell-substrate contact, Yoda1 can be used to activate the channels in endothelial cells without applying an exogenous force 24 that might otherwise complicate the analysis by concurrently stimulating parallel mechanisms.…”
Section: Introductionmentioning
confidence: 99%